2019
DOI: 10.1038/s41598-019-48443-3
|View full text |Cite
|
Sign up to set email alerts
|

Oil palm concessions in southern Myanmar consist mostly of unconverted forest

Abstract: The increased demand for palm oil has led to an expansion of oil palm concessions in the tropics, and the clearing of abundant forest as a result. However, concessions are typically incompletely planted to varying degrees, leaving much land unused. The remaining forests within such concessions are at high risk of deforestation, as there are normally no legal hurdles to their clearance, therefore making them excellent targets for conservation. We investigated the location of oil palm plantations and the other m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 34 publications
2
18
0
Order By: Relevance
“…Moreover, we developed a code to pre-process radar and optical datasets, as well as classify land-cover entirely in the Google Earth Engine. The improved accuracy for detecting oil palm plantations with the use of optical and radar data highlights the importance of multisensory and data fusion techniques, which integrate multiple data features to improve map detail and accuracy [60]. This is especially important in the tropics, where oil palm plantations expand most and where optical-based mapping is limited due to high extents of cloud cover.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we developed a code to pre-process radar and optical datasets, as well as classify land-cover entirely in the Google Earth Engine. The improved accuracy for detecting oil palm plantations with the use of optical and radar data highlights the importance of multisensory and data fusion techniques, which integrate multiple data features to improve map detail and accuracy [60]. This is especially important in the tropics, where oil palm plantations expand most and where optical-based mapping is limited due to high extents of cloud cover.…”
Section: Discussionmentioning
confidence: 99%
“…In Borneo, for example, annual commercial plantation expansion has been found to be positively correlated with annual forest loss [ 73 ]. It is also evident that land use in some regions of Myanmar has shifted to rubber, betel nut, cashew and oil palm [ 35 ], [ 74 ], all of which needs conversion of abundant land areas [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…As planted/cultivated area is subsequently rebounding during the same period, the afforestation pattern might be contributed by agricultural expansion. Commercial agriculture has been used as opportunities by Military to con scate abandoned lands and develop large-scale plantations of crops after the con ict (Lim et al 2017;Nomura et al 2019; Kevin M. Woods 2019). In this research, several new establishments assumed to be military campsite are shown on the maps.…”
Section: Discussionmentioning
confidence: 99%